Studi Kualitatif Tentang Pengalaman Perawat Merawat Pasien Covid-19 - Siti Khamdiyah; Ragil Setiyabudi (FORIKES, 2021)
The Covid-19 pandemic has made nurses experience changes in their work and lives. This study aims to determine the experience of nurses in treating Covid-19 patients, using a phenomenological approach. This study involved 10 informants. Data were collected through social media such as Facebook, Instagram, Youtube, regarding the activities of treating Covid-19 patients. The results of the analysis showed 8 themes, namely: heavy workload, fear, anxiety, pride in their work, awareness of responsibility, surrender to God and family support. Keywords: nurse; caring for COVID-19 patients; experience ABSTRAK Pandemi Covid-19 menjadikan perawat mengalami perubahan pada pekerjaan dan kehidupannya. Penelitian ini bertujuan untuk mengetahui pengalaman perawat dalam merawat pasien Covid-19, menggunakan pendekatan fenomenologi. Penelitian ini melibatkan 10 informan. Data dikumpulkan melalui media sosial seperti Facebook, Instagram, Youtube, tentang kegiatan merawat pasien Covid-19. Hasil analisis menunjukkan 8 tema yaitu: beban kerja terasa berat, ketakutan, kecemasan, bangga dengan pekerjaannya, sadar akan tanggung jawab, pasrah terhadap Tuhan dan dukungan keluarga. Kata kunci: perawat; merawat psien covid-19; pengalaman